Design, synthesis and cholinesterase inhibitory activity of new dispiro pyrrolidine derivatives. (3rd December 2022) - Mohamed Yusoff, Nadia; Osman, Hasnah; Katemba, Valentia; Abd Ghani, Muhammad Solehin; Supratman, Unang; Che Omar, Mohammad Tasyriq; Murugaiyah, Vikneswaran; Xiang Ren,; Six, Yvan; Azmi, Mohamad Nurul
Abstract: A series of new dispiro pyrrolidines were regioselectively synthesised via [3 + 2]-cycloaddition reactions of 3, 5-bis(arylidene)-1-phenylethyl-4-piperidones with azomethine ylides generated in situ from N -methylglycine and appropriate isatin derivatives. The structures of the synthesised compounds were characterized by NMR, FT-IR and MS. These compounds were assayed in vitro for their inhibitory activity against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), using Ellman's assay. The results demonstrate better inhibitory activity against butyrylcholinesterase as compared to acetylcholinesterase. Compound 7b exhibits potential as a new BChE inhibitor, with an IC50 of 12.78 ± 1.52 μM. A kinetic study suggests 7b as a mixed-mode inhibitor, where the active molecule can bind to the active or allosteric sites of the enzyme. An in silico study was performed using AutoDock Vina to identify the binding energy and conformation of 7b with the crystal structure of BChE complexed with Thioflavin T (PDB ID: 6ESY) and the crystal structure of human AChE complexed with dihydrotanshinone 1 (PDB ID: 4M0E). The results indicate better binding properties of 7b compared with the standard inhibitor Thioflavin T, with calculated binding energies of −13.9 and −9.7 kcal mol-1 for BChE and AChE, respectively. Graphical abstract: Image 1 Highlights: A new series of dispiro pyrrolidines were synthesised and characterized. Compound 7a-d and 8a-d were evaluated for in vitro α-amylase and α-glucosidase inhibitory activity. Compound 7b was found good BChE inhibitor with IC50 of 12.78 ± 1.52 μM compared to acetylcholinesterase. Kinetic studies suggested compound 7b represented as a mixed a mixed-mode inhibitor, where the active molecule can bind to the active or allosteric sites of the enzyme. In silico study for 7b show better binding properties compared with the standard inhibitor Thioflavin T.